Proposal of a Planar Directional UWB Antenna for Any Desired Operational Bandwidth - Marco A. Peyrot-Solís; Giselle M. Galvan-Tejada; Hildeberto Jardon-Aguilar (International Journal of Antennas and Propagation)
A novel planar directional UWB antenna is proposed. The antenna design evolves from an oblique elliptic cone antenna by applying the planar-solid correspondence to two axes. Through a simple equation, this antenna can be designed, to operate at a specific lower cutoff frequency with a bandwidth larger than 10 GHz for a reflection coefficient magnitude lower than −10 dB. This characteristic provides the antenna with a good versatility. The directional radiation pattern has an average gain of 6 dBi.